2021
DOI: 10.1111/jvim.16267
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal ultrasound and clinicopathologic findings in 22 cats with exocrine pancreatic insufficiency

Abstract: Background Awareness of exocrine pancreatic insufficiency (EPI) in cats has increased since the development of an assay for feline trypsin‐like immunoreactivity (fTLI). Ultrasound findings in cats with EPI have only been reported rarely and described as nonspecific. Hypothesis/Objectives To describe the ultrasonographic findings, clinical signs, and concurrent diseases in cats with EPI. Animals Twenty‐two client‐owned cats with EPI. Methods Multicenter retrospective descriptive study including cats with serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…90 g/m in both groups, which indicates that the intestinal wall thickness did not differ between the groups and that an actual growth of the intestine in the PL animals can be assumed. Previous studies found by histological or ultrasonographic examination either no effect on intestinal wall thickness due to EPI or an increase in intestinal wall thickness in EPI patients (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 92%
“…90 g/m in both groups, which indicates that the intestinal wall thickness did not differ between the groups and that an actual growth of the intestine in the PL animals can be assumed. Previous studies found by histological or ultrasonographic examination either no effect on intestinal wall thickness due to EPI or an increase in intestinal wall thickness in EPI patients (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 92%
“…Few retrospective studies have investigated signalment, clinical signs, and concurrent diseases in cats with exocrine pancreatic insufficiency (EPI) 74,82 . They highlight EPI as an important differential diagnosis of CE in cats.…”
Section: Resultsmentioning
confidence: 99%
“…From an epidemiological point of view, our data confirm what is reported in the literature: German Shepherds were the most affected breed (35%), but no other breed predisposition was identified in this study. Associations with EPI and dog breed were found in German Shepherds, rough-coated collies, Chow Chows, and Cavalier King Charles Spaniels [4][5][6][7][8][9]. PAA is the most common cause of severe EPI in German Shepherds [4,9,24], rough-coated collie [25,26], and English setter [27].…”
Section: Discussionmentioning
confidence: 99%
“…The first is an autoimmune disorder, called pancreatic acinar atrophy (PAA), and it is caused by lymphocytic infiltration of the pancreatic acinar tissue, which leads to active tissue destruction [2,3]; the second is rarer and can be caused by chronic pancreatitis (CP) or pancreatic neoplasia [4]. The most common cause of EPI in dogs is PAA [1], while CP is reported to be an uncommon cause [5], in contrast to humans and cats [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation